2014
DOI: 10.1177/1754337114549876
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic performance and riding posture in road cycling and triathlon

Abstract: Cycling performance is strongly dependent on aerodynamic drag, of which the majority is attributable to the rider. Previous studies have shown the importance of optimising athlete posture on the bicycle for individual time-trial events. This article identifies that performance in road cycling and draft-legal triathlon can be improved through aerodynamic optimisation of the athlete’s posture. Nine relevant cycling postures have been studied, and it was found that for road cycling, gripping the hoods with horizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 25 publications
2
35
1
Order By: Relevance
“…Broker [61] and Kyle [62] note that rider positions that result in a flat back, a low tucked head and forearms positioned parallel to the bicycle frame generally have low aerodynamic drag. Wind tunnel investigations into a wide range of modifications to standard road cycling positions by Barry et al [55] showed that that lowering the head and torso and bringing the arms inside the silhouette of the hips reduced the aerodynamic drag. Positions that resulted in reductions in aerodynamic drag were also related to a lower velocity deficit and turbulence levels in the wake.…”
Section: Wind Tunnel Testing Of Rider Positionmentioning
confidence: 99%
“…Broker [61] and Kyle [62] note that rider positions that result in a flat back, a low tucked head and forearms positioned parallel to the bicycle frame generally have low aerodynamic drag. Wind tunnel investigations into a wide range of modifications to standard road cycling positions by Barry et al [55] showed that that lowering the head and torso and bringing the arms inside the silhouette of the hips reduced the aerodynamic drag. Positions that resulted in reductions in aerodynamic drag were also related to a lower velocity deficit and turbulence levels in the wake.…”
Section: Wind Tunnel Testing Of Rider Positionmentioning
confidence: 99%
“…While several studies have examined CdA in road cycling, [8][9][10][11][12] very few have focused on sprinting. 1,6 To the best of our knowledge, this is the first study assessing CdA of a novel forward standing position.…”
Section: Discussionmentioning
confidence: 99%
“…different positions was not the focus of these studies. 1,6 From data published on aerodynamics in cycling, it is known that lowering the torso [8][9][10][11] and head 9,12 significantly reduced aerodynamics. Therefore, in this study a novel cycling sprint position was assessed during which participants adopted a low and forward torso and head position (forward standing position).…”
mentioning
confidence: 99%
“…The optimum torso angle for each athlete varied from 1.6° to 8.6° to the horizontal plane. Barry et al [23] performed wind tunnel tests to investigate the effect of variations in body posture on aerodynamic performance. The torso angle of the athlete was also investigated in dropped positions.…”
Section: Introductionmentioning
confidence: 99%